Evaluation of the effects of transcutaneous electrical nerve stimulation on whole saliva flow: A clinical study - Saraf Kedar Vilas; M C Shashikant; I M Ali (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives : Xerostomia and salivary gland hypofunction are associated with advancing age, autoimmune diseases such as Sjφgren's syndrome, head and neck radiation, smoking and recreational drug usage. Palliative management of xerostomia includes topical agents such as ice chips, saliva substitutes, increasing water intake, paraffin and citric acid containing lozenges. Systemic agents have been used, but some drugs have been found to have unfavorable side effects. Therefore, this study was undertaken to evaluate the effect of transcutaneous electrical nerve stimulation (TENS) on whole salivary flow rate in healthy adult subjects. Study Design : One hundred healthy adult subjects (50 males and 50 females), with no history of salivary gland disorder, were enrolled in this study. TENS electrode pads were placed externally on the skin overlying the parotid glands. Unstimulated whole saliva was collected for five minutes in a graduated tube, using a standardized collection technique. The TENS unit was then activated and stimulated saliva was collected for an additional five minutes. Results : Eighty five of the 100 subjects demonstrated increased whole salivary flow when stimulated via the TENS unit. Eleven experienced no change and four experienced a decrease in the salivary flow. The mean unstimulated salivary flow rate was 0.36 ml/min (SD 0.16) and there was a 21% increase in the salivary flow following TENS application. Statistical analysis of flow rates utilizing the paired 't' test showed the difference to be statistically significant (P< 0.001). Interpretation and Conclusion : The TENS unit was effective in increasing whole salivary flow in 85% of the healthy adult subjects. A further study in patients with xerostomia, secondary to various local and systemic causes, is required.